Kinerja return teknologi dan suku bunga - Wardahana, I Made Vareldya Indra; Tiranda, Marvelino Alesandro (Riset Akuntansi dan Manajemen Pragmatis, 2023)
Changes in interest rates in Indonesia tend to produce certain phenomena in capital market conditions. Especially in the technology sector, share prices tend to have a decreasing pattern as interest rates increase. This study takes the period from 24 November 2022 to 16 February 2023 or the period where there was an increase in interest rates. The findings show that technology sector returns have a weak and unidirectional relationship with interest rates, although it is not significant. This implies that returns from the technology sector tend to increase as interest rates increase.